Research of the problem of the high prime price of the edition at the print on demand - Юданова, Алиса Юрьевна; Бизюк, Андрей Валериевич (Eastern-European Journal of Enterprise Technologies, 2011)
The article is devoted research of decisions of problem of high prime price of edition at a print on demand. Research of question about the decision of problem is produced the method of analysis of hierarchies taking into account the criteria of estimation